2012
DOI: 10.1016/j.neurobiolaging.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/enhancer binding protein delta (CEBPD) elevating PTX3 expression inhibits macrophage-mediated phagocytosis of dying neuron cells

Abstract: The CCAAT/enhancer binding protein delta (CEBPD, C/EBPδ, NF-IL6β) is induced in many inflammation-related diseases, suggesting that CEBPD and its downstream targets may play central roles in these conditions. Neuropathological studies show that a neuroinflammatory response parallels the early stages of Alzheimer's disease (AD). However, the precise mechanistic correlation between inflammation and AD pathogenesis remains unclear. CEBPD is upregulated in the astrocytes of AD patients. Therefore, we asked if acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 63 publications
5
91
0
Order By: Relevance
“…We also noted that expression of TSG-6, 18 PTX3, MMP-1, and MMP-3 transcripts was all upregulated by TNF-a and IL-1b in a manner similar to overexpression of CCAAT/enhancer binding protein delta (CEBPD) in U373MG cells. 40 To resolve their interrelationship, we used PTX3 knockdown to demonstrate further upregulation transcription and activation of MMP-1 and MMP-3 in normal and CCh fibroblasts (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…We also noted that expression of TSG-6, 18 PTX3, MMP-1, and MMP-3 transcripts was all upregulated by TNF-a and IL-1b in a manner similar to overexpression of CCAAT/enhancer binding protein delta (CEBPD) in U373MG cells. 40 To resolve their interrelationship, we used PTX3 knockdown to demonstrate further upregulation transcription and activation of MMP-1 and MMP-3 in normal and CCh fibroblasts (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…The microglia-mediated Aβ clearance by phagocytosis has been mentioned (Simard et al, 2006;Lee and Landreth, 2010) but the phagocytotic activity is reduced in AD patients (Fiala et al, 2005;Fiala et al, 2007). The activation of astrocytic CEBPD was thought to attenuate the macrophage-mediated phagocytosis of damaged neurons and regulate the migration and activation of microglia and macrophages (Ko et al, 2012;Ko et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Several studies have suggested that the p38/CREB (cAMP responsive element binding protein) and JAK/ STAT3 pathways play crucial roles in CEBPD transcriptional activation (10,11). Previous studies have also suggested that CEBPD plays a vital role in inflammation and inflammatory disease processes (12,13). However, unlike the inflammatory effectors NF-kB and STAT3 that are consistently activated in cancer cells, CEBPD inactivation has been observed in several types of cancer, including cervical and hepatocellular carcinoma (10,14), breast (15), prostate cancer (9), and leukemia (16).…”
Section: Introductionmentioning
confidence: 99%